The Archaeology and Heritage of the First World War and the Wars of Independence in Lithuania: The State of Research and Future Prospects - Gediminas Petrauskas (Acta Historica Universitatis Klaipedensis)
The archaeological investigations of First World War sites that began in the United Kingdom at the turn of the 20th and 21st centuries expanded the concept of Great War research, laid the foundations for the development of modern conflict archaeology, and shaped its theoretical and methodological approaches. In Lithuania, the sites of the First World War (1914–1918) and the Wars of Independence (1919–1920) have not attracted much interest among researchers, and there are almost no published studies to date. This article focuses on the legacy of the First World War and the Wars of Independence in Lithuania, for the first time providing an overview of the archaeological research carried out up to 2023 in trenches, battlefields, and sites of death and burial, analysing the context of the research and presenting its results. Drawing on the experience of the archaeology of the First World War in other countries, the author discusses the state of the research and its future prospects, and offers a definition of the archaeology of the First World War and the Wars of Independence in Lithuania.